2012
DOI: 10.1590/s0100-72032012001100003
|View full text |Cite
|
Sign up to set email alerts
|

Prognóstico obstétrico de pacientes portadoras de diabetes mellitus pré-gestacional

Abstract: Sílvia maRgaRida duaRte teixeiRa gueRRa aRagüéS 3 njila Yakalage baRReiRa amaRal 3 Resumo OBJETIVO: Avaliar as alterações epidemiológicas, de perfil clínico e de prognóstico obstétrico em pacientes portadoras de diabetes mellitus pré-gestacional. MÉTODOS: Estudo retrospetivo (coorte) de todas as gestações simples, com diagnóstico de diabetes prévio que foram seguidas num centro com apoio perinatal diferenciado entre 2004 e 2011 (n=194). Analisaram-se tendências relacionadas com dados demográficos e variáveis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Diabetic pregnancy, defined as either maternal preexisting diabetes (types 1 and 2 diabetes) or gestational diabetes (which occurs only during pregnancy), is related with fetal growth restriction [1]. Offspring of diabetic mothers show a higher rate of diabetes and characteristics of the metabolic syndrome, both strongly associated with premature death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic pregnancy, defined as either maternal preexisting diabetes (types 1 and 2 diabetes) or gestational diabetes (which occurs only during pregnancy), is related with fetal growth restriction [1]. Offspring of diabetic mothers show a higher rate of diabetes and characteristics of the metabolic syndrome, both strongly associated with premature death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Values over 6.5% of glycated hemoglobin are directly associated with foetal loss. A study with diabetic pregnant women at a maternity hospital in Portugal, showed significant occurrence of foetal loss before 24 weeks gestation whose women had elevated levels of glycated hemoglobin (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an association between hyperglycemia and maternal and foetal risks, and increase the value of glycemic is the most important determinant for complications. The most prevalent pregnancy/foetal complications are congenital malformations, miscarriage and macrosomia (2,8,(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevention undertaken by a multidisciplinary team and a good metabolic control before and during pregnancy, provide control of inadequate weight gain and contribute decisively to the improvement of high-risk pregnancies obstetric prognosis [5].…”
Section: Introductionmentioning
confidence: 99%